The Influence of Reading and Listening Skills on the Speaking Ability of Students of the Indonesian Language and Literature Education Study Program at STKIP Mutiara Banten - Arifin Sitio; Rivaldo Siregar (Peneliti.net, 2022)
This study aims to determine the effect of reading and listening skills on the speaking ability of students of the Indonesian Language and Literature Education Study Program at STKIP Mutiara Banten. In this study, data collection was carried out through a survey method by distributing questionnaires to respondents in the STKIP Mutiara Banten environment. The number of samples taken in this study were 60 people. The sampling technique used in this research is non-probability sampling. The method of data analysis used multiple regression analysis with the help of SPSS 24.0. The results of data processing indicate that the variables of reading and listening skills on the speaking ability of students of the Indonesian Language and Literature Education Study Program at STKIP Mutiara Banten. The test parameter for the effect of reading skills on speaking skills shows a significant table value of 0.620 greater r table 0.005 , the effect of listening skills on speaking skills shows a significant table value of 0.646 greater r table 0.005, and the effect of reading and listening skills together shows a significant table value of 0.837, which is significantly greater than r table of 0.005.